ASUHAN KEPERAWATAN PADA KLIEN DENGAN DIAGNOSA MEDIS HIPERTENSI DENGAN MASALAH NYERI AKUT DI WILAYAH CIPAYUNG KOTA DEPOK - Laila Nur Hafizah, (2023)
Background: Hypertension is an increase in systolic blood pressure above 140 mmHg and diastolic above 90 mmHg caused by cardiovascular diseases such as heart disease, stroke and kidney disease. Hypertension can occur by several other factors such as race, age, family history, gender, obesity and lack of physical activity. This research was conducted to find out hypertension and the right way of handling it for sufferers through nursing care for the elderly with hypertension. Methods: This study used a case study approach to see how nurses handled Mr. A who experienced high blood pressure in the Cipayung area, Depok City from February 26 to March 2, 2023. Data collection was carried out by means of interviews, observation and physical examination. Results: Nursing diagnoses on Mr. A is Acute Pain associated with physical injurious agents. Nursing interventions carried out in the form of identifying factors that cause pain, teaching the use of non-pharmacological techniques to reduce pain with progressive muscle relaxation techniques. Nursing implementation is carried out in accordance with nursing interventions that have been made and nursing evaluations are carried out. In 4x visits to Mr. Pain problem. A can be resolved. Conclusion: Nursing care given to Mr. A can be resolved and Mr. A can intervene independently. Keyword : Elderly, Hypertension, Nursing Care